The Influence of Asset Management and Leverage on Dividend Payments With Company Growth as A Moderating Variable in Idxhidiv20 - Stefanie Novelia Samidjaja; I Dewa Nyoman Badera (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Corporate profits may be allocated either as dividends to shareholders or retained to support future investment activities. The proportion of dividends distributed serves as an indicator of management’s ability to balance reinvestment needs with shareholder returns. Decisions regarding dividend distribution are typically finalized during the General Meeting of Shareholders (GMS), following recommendations put forth by the board of directors. This research investigates how asset management influences dividend payments, assesses the impact of leverage on dividend distribution, and explores the moderating effect of company growth on the relationship between asset management and leverage with dividend payouts. The study focuses on companies listed in the High Dividend 20 Index (IDXHIDIV20) from 2019 to 2023. Using purposive sampling, 29 companies were selected, yielding 145 observations that consistently issued dividends throughout the study period. The analysis was conducted using Moderated Regression Analysis (MRA). Findings indicate that asset management positively affects dividend payments, whereas leverage does not exhibit a significant influence. Moreover, company growth is found to weaken the positive association between asset management and dividends, while it does not moderate the relationship between leverage and dividend payouts. These findings support both signaling theory and contingency theory, emphasizing that efficient asset utilization enhances corporate profitability, which in turn can lead to higher dividend distributions.